Working from home during COVID-19 lockdown: Changing competencies and work-home life boundaries - Almeida, J.; Silva, M. G. (Proceedings of the 18th European Conference on Management Leadership and Governance ECMLG 2022, 2022)
Crisis situations often introduces drastic lifestyle changes. This study is focused on the COVID-19 pandemic and aims to shed light on an unprecedented context of forcing employees to work from home with a short notice of companies and the government. The goal is three-fold: i) to understand the extent to which employees were indeed prepared to work from home; ii) to uncover the most important competencies that enabled employees to deal better with a crisis situation, such as the COVID-19 pandemic; and iii) to discuss the real impact that working from home had in the employees’ lives during the pandemic situation and the quarantine period. Using narrative inquiry, this study explores the experiences of 18 young adult consultants working in different business areas, in Portugal. Semi-structure interviews were conducting during the third wave (12/2020 – 03/2021) and thematic analysis was used to analysis the transcripts. The analysis revealed three main themes: ‘management competencies’, ‘work-life balance’ and ‘work flexibility’. Each theme consisted of several subthemes which illustrates how the participants perceived working from home and the factors that reflect their experiences and understanding. The research findings illustrate that interpersonal communication, anxiety and stress management, time management, and e-leadership are vital skills to cause a great impact on participants’ productivity and well-being at work. Participants all appeared to notice that working from home provides a better work-life balance (e.g. saving time on daily commute) and more flexibility with regards to the work schedule and home commitments. Nonetheless, their experiences of home working depend on the personal situation, personality and the perceived management support offered during the COVID-19 lockdown. The research highlights a need to train employees on soft skills and prepare them to future crisis situations. Theoretical implications suggest that academics should expand research and interventions to include not only the work environment but also other external factors that affect employees. The limitations of the study and recommendations for future research are suggested.